2016
DOI: 10.1590/1807-3107bor-2016.vol30.0128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on periodontal pathogens during experimental periodontitis in rats

Abstract: The objective of this study was to investigate the antibacterial effect of resveratrol against putative periodontal pathogens during the progression of experimental periodontitis in rats. Periodontitis was induced in rats in one of the first molars chosen to receive a ligature. Animals were assigned to one of two groups: daily administration of the placebo solution (control group, n = 12) or 10 mg/Kg of resveratrol (RESV group, n = 12). The therapies were administered systemically for 30 days, for 19 days befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…This phenomenon could be linked to the presence of periodontal-pathogens in subgingival biofilm [ 44 ], once the model was described as a plumicrobial infection [ 45 ]. Although the present study has used the ligature-induced periodontitis model and has not performed identification analysis, the microbial profile observed by other authors in the ligature model was similar to that observed in human periodontitis [ 46 , 47 ]. Through a DNA-DNA checkerboard analysis, a previous study identify microbial profile in subgingival environment after ligature-induced periodontitis and found streptococcus- and Actinomyces -like species in high mean counts, followed by Fusobacterium -, Prevotella nigrescens -, Parvimonas micra -, Aggregatibacter actinomycetemcomitans - and Porphyromonas gingivalis -like species [ 47 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This phenomenon could be linked to the presence of periodontal-pathogens in subgingival biofilm [ 44 ], once the model was described as a plumicrobial infection [ 45 ]. Although the present study has used the ligature-induced periodontitis model and has not performed identification analysis, the microbial profile observed by other authors in the ligature model was similar to that observed in human periodontitis [ 46 , 47 ]. Through a DNA-DNA checkerboard analysis, a previous study identify microbial profile in subgingival environment after ligature-induced periodontitis and found streptococcus- and Actinomyces -like species in high mean counts, followed by Fusobacterium -, Prevotella nigrescens -, Parvimonas micra -, Aggregatibacter actinomycetemcomitans - and Porphyromonas gingivalis -like species [ 47 ].…”
Section: Discussionmentioning
confidence: 53%
“…Through a DNA-DNA checkerboard analysis, a previous study identify microbial profile in subgingival environment after ligature-induced periodontitis and found streptococcus- and Actinomyces -like species in high mean counts, followed by Fusobacterium -, Prevotella nigrescens -, Parvimonas micra -, Aggregatibacter actinomycetemcomitans - and Porphyromonas gingivalis -like species [ 47 ]. Another study evaluated the presence and concentrations of Porphyromonas gingivalis , Tannerella forsythia and Aggregatibacter actinomycetemcomitans in the cotton ligatures used to induce periodontitis by real-time PCR and it was possible to identify and quantify all the three species in the analyzed samples [ 46 ]. This reaffirm the reliability of ligature model to mimic the human periodontal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Park and Pezzuto 54 also showed in vitro that RESV attenuated P. gingivalis LPS‐induced monocyte adhesion to the endothelium, suggesting that RESV has a therapeutic role in periodontal pathogen‐induced vascular inflammation. However, a recent experimental study 56 investigating impact of RESV in periodontitis‐associated species during EP revealed that this agent has no antimicrobial properties. Thus, it could be hypothesized that there are other mechanisms through which RESV exerts its promising effects to control periodontitis, as supported by findings of the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis was treated with either resveratrol, curcumin, or their combination . Intergroup comparisons of morphometric outcomes showed higher bone‐loss values in the placebo group ( P < 0.05) compared with the resveratrol, curcumin, and combined groups.…”
Section: Treatment Of Periodontitits With Resveratrol and Its Derivativementioning
confidence: 99%